Efficient iodine sequestration by chemically robust C-C bonded hyper-crosslinked porous organic polymers - Mayakannan G; Karthikkumar R; Himan Dev Singh; Debanjan Chakraborty; Shyamapada Nandi (Chemical Engineering Journal Advances)
Capturing radioiodine from off-gas mixture or contaminated solution is crucial for maintaining environmental safety and public health. However, this is technically challenging because of many factors like low concentration of iodine, harsh operational conditions such as high temperature, presence of high humidity & acidic vapors etc. Herein we report three highly robust hyper-crosslinked porous organic frameworks named IISERP-POF6, IISERP-POF7 and IISERP-POF8 for effective iodine sequestration from the vapour phase as well as solution phase. These polymers not only exhibited an impressive iodine capture capacity (200 mg/g at 25 °C) from a solution having a low iodine concentration (250 mg/L) but also displayed a decent iodine capture capacity (∼2.87 g/g) in the vapour phase at 75 °C. The polymers being chemically robust can be employed in very harsh operating conditions and recycled easily with no loss of iodine capacity. X-ray photoelectron spectroscopy analysis of the I2-loaded polymers indicated the presence of molecular iodine (I2) and polyiodide (I3-/I5-) species in the polymeric frameworks. Density Functional Theory (DFT) studies revealed the interaction of the iodine with the methyl C-H and methylene C-H groups with a short contact distance of 3.4–3.5 Å Additionally, there have been favorable interactions between the π-electron clouds of the monomers such as pyrene, naphthene, and triphenylmethane with iodine/polyiodide species.